Making sense of management innovation in health care - Kortstee, Michiel Jeroen Herman Willem (2018)
This thesis aims at exploring stakeholders’ perceptions of management innovation in health care. Rising health care costs due to technological innovation and demographic developments and advanced insights on how health and care could be organized drive the search for new organizational models and technologies that may contribute to better health outcomes for lower costs. Multiple stakeholders across the health care continuum need to collaborate in integrated care networks with multiple interdependent components. The study is based on qualitative exploratory research and consists of a literature review and a case-study at a management innovation in an university medical center. This study explores the vision and perceptions of stakeholders of innovation in healthcare, the innovation process through which management innovations evolve, underlying change and steering mechanisms, critical success factors and results. Management innovations and their implementation are considered complex. It is observed that due to different backgrounds and professional logics, stakeholders have partial and different understandings of integrated care concepts. Awareness of the different understandings explains the importance of an implementation approach of integrated care concepts where these perceptions converge. Sense making, the attribution of meaning to perceptions is essential here. Change does not happen in a vacuum, but emerges in interaction with other actors in the organization and its local context. It is observed in the literature and case-study that sense making processes are at work in the innovation process. Management innovation is merely a spontaneous, unplanned change process that starts with an intrinsic drive and emerges from how people frame what they see, relate it to their values and act upon it in interaction with others. It is a human, subjective, interactive, emergent selforganizing process of sensing and sense making that – if aligned with vision, values and intentions of people – can bring together different stakeholders in joint concepts of integrated care. Leading management innovation processes becomes a matter of guiding and creating room for self-organizing processes in organizations. Examples of management innovation from across the world demonstrate that management innovation can significantly contribute to better health outcomes for lower costs. The willingness, necessity and ability to change determine the pace. Exploring further and investing in the potential of management innovation may be a wise choice to make health systems more sustainable.